Ensino de Entropia: um enfoque histórico e epistemológico. - Santos, Zanoni Tadeu Saraiva dos (2010)
The rational construction necessary to systematize scientific knowledge in physics, introduces difficulties of understanding in some of its concepts. One of these concepts which exemplify properly this difficulty in learning or teaching is entropy. This thesis propose the construction of a didactic route which constitute itself a historical and epistemological course to entropy, intending to contribute for teaching this concept as well as other physics concepts. The basic assumption to build this route is that through the historical review of the development of this concept in the way suggested by Bachelard s (1884-1962) epistemology it is possible to make subjects, to be taught and learned, more meaningful. Initially I composed a brief biographical note to give the reader an idea about the issues, interests and reflections, related to science, and how I dealt with them in my private and professional life, as well as the role they played to lead me to write this thesis. The strategy to construct the route to entropy was to split the usual contents of basic thermodynamics in three moments in a way they can constitute epistemological units , which can be identified by the way of thinking in the corresponding moments of scientific knowledge production: a technical and empiricist moment, a rationalist and positivist moment and a post-positivist rationalist one. The transition between each moment is characterized by a rupture with the former way of thinking; however the progress in the construction of knowledge in the area is evident. As the final part of this work I present an analysis based on elements of Bachelard s epistemology that are present in each moment. This analysis is the basic component of the didactic route that I propose myself to build. The way I made this route guide to entropy could contribute to the construction of other didactic routes in physics and other sciences, in a way to unveil hidden meanings and as a tool to humanize scientific knowledge.